THE ANALYSIS ON TRANSLATION TECHNIQUES AND TRANSLATION QUALITY OF CHINESE CULTURE SOCIAL TERM - Ayu Kharisma Maharani (Prasasti: Journal of Linguistics)
The Chinese cultural term is one of the main problems in translation. This study aims to analyze the translation which is the Chinese social cultural term, translation techniques, and the impact of the use of translation techniques on the quality of translation which includes aspects of accuracy, acceptability, and readybility. This research employs a descriptive qualitative with case study and oriented to the translation product. The source of data take from documents selected with purposive sampling technique and the discussion result with raters and informant. The document refer to Stempel Tiongkok:  Kumpulan Karya Li Lanqing Dalam Pameran Seni Ukir dan Kaligrafi with its translated text. Data reaserch contains Chinese culture term which are word or phrase. The technique of collecting data used consisted of analysis of documents, quisioner and interview to raters and informants. Data were analyzed using ethnographic analysis, which consisting of domain, taxonomy, and componential analysis until found its cultural theme. From the analysis found 12 data and 7translation technique. They are using adaptation techniques, lending, common equivalent, linguistic compression, variation, deskrutif creation, transposition. Good translation techniques are common equivalent, linguistic compression, lending, variation. Translation techniques are not good deskrusif creations and adaptations.